4-(Furan-2-carbonyl)piperazin-1-ium 3,5-dinitrobenzoate - Kavitha, Channappa N. (International Union of Crystallography, 2014)
In the cation of the title salt, C(9)H(13)N(2)O(2) (+)·C(7)H(3)N(2)O(6) (−), the piperazine ring adopts a slightly distorted chair conformation. Twofold rotational disorder is exhibited by the furan ring in a 0.430 (4):0.570 (4) ratio. In the crystal, N—H⋯O hydrogen bonds link the ions into chains along [010]. Additional weak C—H⋯O interactions are observed, leading to a supramolecular layer parallel to (011).